The Effect of AEC in Shaping Entrepreneurial Motivation for Vocational High School Prospective Graduates - Prihatna, Kusumah Arif (Bina Nusantara University, 2017)
This research aimed to investigate the factors forming the motivation of entrepreneurs based on the driving factors outside themselves, namely the existence of a single market of ASEAN Economic Community (AEC). It wastheassumption of the readiness of the students themselves. Basic theory used was the push and pull theory.Thus, with the driving factor, the research also aimed to see the interest factor from within. Respondents were prospective graduate students of Global Persada Vocational High School. Data were collected by distributing questionnaires processed by using quantitative research analysis and multiple linear regression. Partially, it is concluded that the formation of entrepreneurial motivation can be affected by factors of interest and it is not due to the push fromoutside concerning the unpreparedness of students in facing the single market of AEC.